Preparation of near-spherical PA12 particles for selective laser sintering via Plateau-Rayleigh instability of molten fibers. (May 2020) - Zhou, Ying; Xi, Shuting; Huang, Yajiang; Kong, Miqiu; Yang, Qi; Li, Guangxian
Abstract: We report a novel method to prepare near-spherical polyamide 12 (PA12) particles with controllable size for selective laser sintering (SLS) technology based on the Plateau-Rayleigh instability of molten PA12 fibers. In this method, PA12 fibers with desired diameters are first prepared by melt spinning of PA12 pellets. Then, short PA12 fibers after being cropped are dispersed and melted in the hydrosoluble polyethylene oxide (PEO) matrix. During the subsequent thermal treatment process, the molten PA12 fibers spontaneously disintegrate via Plateau-Rayleigh instability and the resultant near-spherical particles are then released by dissolving the PEO matrix with water. In-situ optical microscopy and kinetic analysis based on the Tomotika's model indicate that the diameter of particles is mainly determined by that of fibers while the transformation dynamics depend largely on the temperature of thermal treatment. The utilization of a two-step thermal treatment can effectively accelerate the fiber-to-particle transformation dynamics. The powder prepared has an excellent flowability similar to that of commercial powders due to its high degree of sphericity, smooth surface and narrow size distribution. Calorimetry results indicate that the powder prepared had a narrow melting range and wide sintering window. Graphical abstract: Unlabelled Image Highlights: Near-spherical particles with good smoothness, flowability and sinterability are prepared via Plateau-Rayleigh instability. The fiber-to-particle transformation dynamics depend largely on thermal treatment temperature. Particle size is mainly determined by the fiber diameter. The two-step thermal treatment strategy can induce rapid surface undulations and avoid material degradation.